2022
DOI: 10.1088/1742-6596/2366/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature characteristics of FBG with free arc shape for low temperature monitoring

Abstract: It is important to monitor the iced condition for operating wind turbine blades. However, most sensors are difficult to be used in this quite cold and lightweight environment. Although the fiber bragg grating (FBG) is a good candidate for the case. With the change of the temperature, the thermal expansion coefficient and thermo-optical coeffecient of FBG material will affect the accuracy of characteristics of FBG sensor. Aiming at the application of fiber optic sensor in low temperature environment and ultrath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Latka I explored the temperature characteristics of FBG on substrates with different CTE, demonstrating that these special substrates are usable for temperature measurements well below 50K 1 ; Guo ZS investigated the characteristics of strain and temperature of FBG in the temperature range of 123-273 K. Experiments showed that the relationship between wavelength change and temperature can be expressed by a third-order polynomial, and the wavelength is linearly related to the strain, so it is believed that the FBG can realize high-precision strain measurements at low temperatures 2 ; Guo T used FBG connected to an F-P interferometer to realize a large strain measurement of 1.5^10 7 με at low temperatures ranging from 20°C to 70°C 3 ; Yang T researched the strain transfer characteristics of multilayer fiber optic sensor structures at low temperatures, and experiments showed that different temperature loads or lead to different strain transfer errors 4 ; Zhang Z used an FBG strain sensor encapsulated by a double fixture tube and a stainless steel tube for monitoring the structural safety of bridge cranes at low temperatures 5 ; Lu Huanlang investigated the sensing characteristics of encapsulated FBG at low temperatures using a free-arc shape, and experimental results showed that the electric arc shape could improve the precision of fiber shrinkage 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Latka I explored the temperature characteristics of FBG on substrates with different CTE, demonstrating that these special substrates are usable for temperature measurements well below 50K 1 ; Guo ZS investigated the characteristics of strain and temperature of FBG in the temperature range of 123-273 K. Experiments showed that the relationship between wavelength change and temperature can be expressed by a third-order polynomial, and the wavelength is linearly related to the strain, so it is believed that the FBG can realize high-precision strain measurements at low temperatures 2 ; Guo T used FBG connected to an F-P interferometer to realize a large strain measurement of 1.5^10 7 με at low temperatures ranging from 20°C to 70°C 3 ; Yang T researched the strain transfer characteristics of multilayer fiber optic sensor structures at low temperatures, and experiments showed that different temperature loads or lead to different strain transfer errors 4 ; Zhang Z used an FBG strain sensor encapsulated by a double fixture tube and a stainless steel tube for monitoring the structural safety of bridge cranes at low temperatures 5 ; Lu Huanlang investigated the sensing characteristics of encapsulated FBG at low temperatures using a free-arc shape, and experimental results showed that the electric arc shape could improve the precision of fiber shrinkage 6 .…”
Section: Introductionmentioning
confidence: 99%